Retractable Wireless Charging Windings for Inspection Robots - Mohd Norhakim Bin Hassan; Simon Watson; Cheng Zhang (Applied Sciences, 2025)
Limited battery life compromises the usability of inspection and operation robots in hazardous environments such as nuclear sites under decommissioning. Both manually replacing the batteries and installing charging bays may be infeasible. Inductive wireless power transfer is a possible solution to deliver power through barriers such as reinforced concrete walls without physical contact. However, when requiring decent power (e.g., 100 W) to be transmitted over longer distances, the exaggerated dimensions of transmitting and receiving coils restrain the integrations with mobile robots. In this paper, a novel retractable design of the coil used in an inductive wireless power charging system is proposed, proving the minor deformation of the winding shape does not affect the transmission efficiency. A prototype with 5× size compression is implemented and tested. It successfully transmits 116.5 W over a distance of 1 m with 68.72% energy efficiency. The principle can be applied to a wide range of mobile platforms with a limited payload area where remote power is needed.